Livestock Herding in Polish Mountainous National Parks as An Element of Sustainable Regional Development - Kamila MUSIAL (Communications of International Proceedings, 2021)
The study was conducted in 2021, and involved surveys regarding cultural grazing in Poland's mountainous national parks. Cultural grazing is a pasturage of sheep, and cattle in conservation areas, as national parks, with numerous restrictions. In Poland, raising small flocks of sheep for production purposes is considered as an activity of low profitability. However, particularly in the south of the country, pastoralism is seen as an ethnographically attractive, as it is deeply rooted in the traditions of the mountainous regions. This indicates that herding was essential culture-building factor for many centuries. Grazing sheep, and commercializing sheep products may therefore, serve as an excellent way to promote the region in a sustainable way. Sheep herding and grazing on mountain pastures is permanently integrated into the landscape of the Polish mountains, and is an integral part of highland folklore. Promotion of extensive, and cultural grazing is of particular importance in national parks, where grazing helps to slow down ecological succession processes. Moderate intensity grazing by domestic livestock is a potentially beneficial conservation management tool even in protected areas.
Keywords: Cultural Grazing; Conservation Areas; Pastoral Landscape; Polish Mountains